MANAGEMENT ACCOUNTING PRACTICES IN THE PUBLIC SECTOR: A SYSTEMATIC LITERATURE REVIEW ON POSITIVE OUTCOMES AND NEGATIVE OUTCOMES - Purnama, Zuardiansyah Adi; Fuadah, Luk Luk (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This article presents a systematic review of the development of management accounting practices (MAPs) in the public sector through an analysis of 29 Scopus-indexed articles from high-impact journals (Q1 and Q2) published between 2020 and 2024. The research findings reveal that the implementation of MAPs has contributed to increased transparency through Integrated Reporting and operational efficiency using techniques such as Activity-Based Costing. However, its implementation still faces various challenges, including financial statement manipulation, privacy issues, and resistance to change. This review also identifies a diversity of theories underlying MAPs research, such as New Public Management, Institutional Theory, and Stakeholder Theory. The study provides academic contributions by synthesizing recent findings and offers practical recommendations for stakeholders in the public sector.